Monitoring seasonal changes in body composition and physical performance in elite female soccer players - Zabaloy, S.; Villaseca-Vicuña, R.; Freitas, T. T.; Loturco, I. (The Journal of Strength and Conditioning Research, 2026)
This study aimed to investigate seasonal changes in body composition and physical performance in elite female soccer players. Thirty-two professional players (age: 26 ± 4 years) from the same club were assessed at 3 time points (TPs): preseason (TP1), early in the season (TP2), and midseason (TP3). For approximately 6 months, players completed anthropometric and body composition assessments, and physical tests including the countermovement jump (CMJ), squat 1 repetition maximum (squat 1RM), 10-m sprint, and Yo-Yo Intermittent Recovery Test Level 1 (YYIR1). Mean propulsive velocity (MPV) during the squat exercise was assessed at absolute loads of 30 and 40 kg. Significant and gradual improvements were observed in sum of 6 skinfolds, fat mass percentage, and muscle mass percentage (p < 0.02). Mean propulsive velocity at 30 and 40 kg increased significantly throughout the season (p < 0.039), while 1RM and relative strength remained stable. Countermovement jump, 10-m sprint, and YYIR1 performance improved significantly from TP1 to TP3 (p < 0.003), with YYIR1 showing very large gains (˜25%). These adaptations occurred despite a congested competition schedule, with players participating in 18 matches across the study period. Overall, the findings indicate that a multicomponent training program combining resistance, power, speed, and endurance sessions can improve body composition, neuromuscular qualities, and endurance performance during the early and midseason stages in professional female soccer players. The results provide novel insights into performance monitoring in female soccer and highlight the importance of integrating diverse physical training strategies throughout the competitive season.